From heritage to innovation: the Arxiu Valencià del Disseny as a strategic resource for contemporary design - Alba-Pagán, Ester; Pitarch-Garrido, Mª Dolores; Gaitán-Salvatella , Mar; León-Muñoz, Arabella (Arte, Individuo y Sociedad, 2026)
This paper analyses the role of the Arxiu Valencià del Disseny (AVD) as a driving force behind an innovative design ecosystem in the Valencian Community. Using a qualitative methodology based on focus groups with senior designers, young designers and teachers, it examines the perceptions and uses of the archive by the main players in the sector. The results confirm that the AVD is perceived as a key resource for the conservation of Valencian design heritage, as well as a strategic tool for training, research and professional practice. However, significant challenges related to the visibility, accessibility and institutional links of the archive are identified. A set of actions is proposed to enhance its impact, such as collaboration with educational and business entities, technological improvement and international projection. The study concludes that the AVD not only preserves the memory of design, but also has the potential to become a hub for innovation and sustainable development in the field of regional design.
Keywords: design; innovative ecosystems; Arxiu Valencià del Disseny; Valencian Community